Dynamic Impacts of Climate and Land-Use Changes on Surface Runoff in the Mountainous Region of the Haihe River Basin, China - Ruonan Li; Hua Zheng; Binbin Huang; Huashan Xu; Yunkai Li (Advances in Meteorology)
The relative contributions of different factors to the variation in surface runoff have been broadly quantified. However, little attention has been paid to how these relative contributions have changed over time. We analyzed the changes in surface runoff during 1980–2010 in six subbasins in the mountainous region of the Haihe River Basin, one of the most serious water shortage regions in China, and identified the changes in the relative contributions of climate (precipitation and temperature) and land-use to surface runoff decrease. There was a decreasing tendency in surface runoff in all subbasins, four of which had an abrupt change point around 1998. Comparing the relative contributions before and after 1998 in the four subbasins, the average influence of climate was found to decline dramatically from 67.1% to 30.5%, while that of land-use increased from 23.9% to 69.5% mainly due to the increase of forest area. Our results revealed that the primary environmental factor responsible for runoff variations was not constant, and an alternation may accentuate the impact and stimulate an abrupt change of runoff in semiarid and semihumid mountainous regions. This will help in taking tracking measures to deal with the complex water resource challenges according to different driving factors.